Exploring the impact of product service quality on buyer commitment and loyalty in B TO B relationships. Issue 2 (3rd April 2018) - Kim, Sung Hong; Kim, Jin Han; Lee, Won Jun
ABSTRACT: Purpose : The purpose of this study is to understand and empirically test causal relationships among components of product service quality and commitment and buyer loyalty in business-to-business (B to B) relationships. Methodology/approach : Data were collected through a web-based survey from 314 buyers of B to B manufacturers in Korea. Findings : Product quality enhances all three types of commitment in B to B relationships, service quality is positively associated with affective commitment, and support quality has a significantly positive effect on affective and normative commitment. Also, the moderating effects of competitive intensity are significant. If competitive intensity is low in the buyer's market, product quality and service quality play important roles in deriving buyer commitment; however, if competitive intensity is high, support quality is effective in maintaining long-term committed relationships with buyers. Research implications : To fully consider product service quality in this study, we established support quality, product quality, and service quality as discrete components of product service quality. Practical implications : Previous quality-related works have focused on products and services with little research about support activities, and the literature is lacking empirical analyses of support activities. However, this study elucidates the importance of operational and technical support activities in B to B relationships. Specifically, in a fiercely competitive market, a high-quality consumer support strategy is shown to be highly effective in maintaining long-term committed relationships with buyers. Originality/value/contribution : We analyzed the relationships among components of product service quality and commitment and buyer loyalty in B to B transactions. Our detailed results will help firms develop context-specific quality management strategies at the product service level in order to strengthen customer loyalty.